1982
DOI: 10.1093/nar/10.22.7283
|View full text |Cite
|
Sign up to set email alerts
|

Transcripts of mitochondrial tRNA genes inSaccharomyces cerevisiae

Abstract: The transcription of a group of tRNA genes from the large tRNA gene cluster of mitochondrial DNA from Saccharomyces cerevisiae hase been investi gated by hybridization with DNA probes carrying t coding sequences and small portions of the A+T rich intergenic regions.Results have shown that in some rho mutants (DS502, Fll) mature tRNA was absent, but a few transcripts could be detected. Some high molecular weight species actually hybridized with DNA probes carrying different tRNA coding sequences. Low molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1984
1984
1994
1994

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…The first (very faint) signal (indicated by an open circle in Figure 4, lane 11) corresponded to a transcript terminating at the 3' end of the tRNAArg gene, while the second (very strong one, indicated by a dot in Figure 4, slot 11 and 13) corresponded to a transcript terminating at the 3' end of the tRNALys gene. A diagrammatic representation of the transcripts mapped in these and previous experiments (Frontali et al, 1982) is shown in Figure 5. Figure 2, 3 and 6a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first (very faint) signal (indicated by an open circle in Figure 4, lane 11) corresponded to a transcript terminating at the 3' end of the tRNAArg gene, while the second (very strong one, indicated by a dot in Figure 4, slot 11 and 13) corresponded to a transcript terminating at the 3' end of the tRNALys gene. A diagrammatic representation of the transcripts mapped in these and previous experiments (Frontali et al, 1982) is shown in Figure 5. Figure 2, 3 and 6a).…”
Section: Resultsmentioning
confidence: 99%
“…Lanes were as follows: (1) The smallest transcript (130 nucleotides), which has not been detected in w.t. cells, has previously been shown to contain the sequence of tRNAHis and the upstream intergenic sequence up to the 3' end of the preceding tRNAcys gene (Frontali et al, 1982).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial DNA deletion mutants that lack this locus accumulate tRNA precursors (6,11,23,24). Characterization of tRNA gene transcripts in such mutants shows that they are correctly processed on the 3' end but retain 5' tRNA precursor leader sequences (13).…”
mentioning
confidence: 99%
“…Transcript mapping shows that other 5' tRNA leaders result from cleavage events that separate precursors * Corresponding author. from polycistronic RNA molecules (6,20,24). tRNA precursors of both origins require the tRNA synthesis locus for 5' leader processing (23).…”
mentioning
confidence: 99%